Development and optimisation of multi-nozzle spray manufacturing process for black seed oil alginate beads - Shaiqah Mohd Rus (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2022)
Black seed oil (BSO) is a natural remedy derived from Nigella sativa Linn. The main active ingredient in BSO, thymoquinone, is well-known for its antibacterial and antioxidant properties. Prophet Muhammad (PBUH) stated that black seed is one of the remedies for all diseases except death. However, consumers find it difficult to take BSO on a daily basis due to its bitter taste. BSO's bitter taste is hidden by encapsulating it in a soft gelatine capsule. However, because of the capsule's size, children and the elderly have difficulty swallowing it. BSO is encapsulated in micrometre-sized alginate beads to increase palatability in individuals of all ages, particularly children and the elderly. This research aims to encapsulate BSO in alginate beads made with a multi-nozzle spraying method that has the same quality and characteristics as a single nozzle. From the results, the overhead stirrer combined with homogeniser and flow cell sonicator with a minimum amplitude of 20 produced the best droplet size, PdI, and dissolution time of BSO alginate nanoemulsion. The flow rate and applied voltage significantly influenced the diameter of BSO alginate beads (p-value < 0.05). The sphericity factor (SF) was unaffected by flow rate, applied voltage, or distance between the nozzle and the cross-linking solution. Thus, the optimisation of the mixing, emulsification and electrospraying process was successfully done on the lab scale. The first and fifth designs showed the best maldistribution factor (MF) value, near-zero MF value, in designing and analysing a 3D-printed pilot-size multi-nozzle prototype for the electrospraying process at the lab scale. The fifth design was chosen, and this is the first multi-nozzle with two baffles in the core, combining two different types of the best baffle designs. The results showed that a multi-nozzle spray produced a good SF value and beads size without utilising high voltage. Equipment involved in the BSO alginate beads manufacturing line was optimised at the IKOP® Sdn. Bhd pilot plant. The 100 L mixing tank equipped with stirrer and homogeniser at 500 and 1500 rpm speed, respectively was capable of reducing the droplet size. To process a greater volume with the least amount of energy, BSO alginate nanoemulsion was produced using flow configuration at the best process parameters obtained from pilot plant study. Using a 70% amplitude power rather than 90% to produce BSO alginate nanoemulsion at a flow rate of 72, 144, 216, or 288 mL/min is advisable due to less energy consumption. The critical quality attribute of BSO alginate nanoemulsion, which were particle size and PdI, was accomplished using both amplitude powers. The difference between the top and bottom of a 20-litre holding tank is 7.18 %, thus within in-process quality control (IPQC) target. From the data, 83.33 % of the beads have an SF of less than 0.05, which was above the IPQC's goal which is more than 75 % of the beads having an SF of less than 0.05. The IPQC beads diameter range is between 1.50 mm to 2.50 mm, and all BSO beads diameter readings are within that range. The multi-nozzle spray apparatus achieved successful outcomes by producing wet beads with an SF of less than 0.05. Hence, the multi-nozzle spray machine can manufacture BSO alginate wet beads in large quantities. The curing with filter tank placed at IKOP® Sdn. Bhd. was capable of curing and filtering the BSO alginate beads production process where it met the goal of a continual decrease in calcium ion concentration. Finally, this study successfully developed and optimised the multi-nozzle spray production line in producing BSO alginate beads with same quality and characteristics as a single nozzle in the lab scale.